Potentiality of Eisenia fetida to degrade disposable paper cups—an ecofriendly solution to solid waste pollution - Arumugam, Karthika; Ganesan, Seethadevi; Muthunarayanan, Vasanthy; Vivek, Swabna; Sugumar, Susila; Munusamy, Vivekanadhan (Environmental science and pollution research international, 2015)
The aim of the present study was to subject the post-consumer waste, namely paper cups for vermicomposting along with cow dung in three different ratios for a period of 90–140 days employing Eisenia fetida. The post-consumer wastes are a menace in many developing countries including India. This waste was provided as feed for earthworms and was converted to vermicompost. Vermicompost prepared with paper cup waste was analyzed for their physicochemical properties. Based on the physicochemical properties, it was evident that the best manure is obtained from type A (paper cup/cow dung in the ratio 1:1) than type B (paper cup/cow dung in the ratio 1.5:0.5) and type C (paper cup/cow dung in the ratio 0.5:1.5). The results showed that earthworms accelerated the rate of mineralization and converted the wastes into compost with needed elements which could support the growth of crop plants. The predominant bacterial strains in the vermicompost were characterized biochemically as well as by 16S ribosomal RNA (rRNA) gene sequencing. The bacterial strains like Bacillus anthracis (KM289159), Bacillus endophyticus (KM289167), Bacillus funiculus (KM289165), Virigibacillius chiquenigi (KM289163), Bacillus thuringiensis (KM289164), Bacillus cereus (KM289160), Bacillus toyonensis (KM289161), Acinetobacter baumanni (KM289162), and Lactobacillus pantheries (KM289166) were isolated and identified from the final compost. The total protein content of E. fetida involved in vermicomposting was extracted, and the banding pattern was analyzed. During final stages of vermicomposting, it was observed that the earthworm did not act on the plastic material coated inside the paper cups and stagnated it around the rim of the tub. Further, the degradation of paper cup waste was confirmed by Fourier transform infrared spectroscopy analysis. Hence, vermicomposting was found to be an effective technology for the conversion of the paper cup waste material into a nutrient-rich manure, a value-added product.